Pengaruh Efektivitas Komite Audit dan Penghindaran Pajak: Peran Moderasi Kualitas Audit - Purnomo, Hanny; Eriandani, Rizky (E-Jurnal Akuntansi; Vol 32 No 7 (2022)DO - 10.24843/EJA.2022.v32.i07.p06, 2022)
As a component of corporate governance, the audit committee and external auditors have functions as independent supervisors on financial reports, risk management and overseeing the company's compliance with laws and regulations. This study examines the relationship between the effectiveness of the audit committee on corporate tax avoidance and the moderating role of audit quality. Using purposive sampling technique, this study tested 215 manufacturing companies for the period 2019-2021 using multiple linear regression analysis techniques. This study shows the results that an effective audit committee along with audit quality can reduce corporate tax avoidance activities. Keywords: Effective Audit Committee; Audit Quality; Tax Avoidance.